Komunikasi Interpersonal Antar ODHA untuk Menumbuhkan Motivasi Kembali Hidup Normal di Yayasan Mahameru Surabaya - Huda, Jesica Miftakhul; Prasetyo, Iwan Joko; Fitriyah, Irmia (Jurnal Komunikasi Profesional, 2019)
This study aims to find out how interpersonal communication occurs between PLWHA (people with HIV / AIDS) to foster motivation to return to normal life in the mahameru foundation of Surabaya. The Mahameru Foundation is the only non-profit institution in Surabaya that is engaged in the social and humanitarian field focusing on the mentoring and empowerment program for PLWHA. There are so many new PLHIV who experience a decrease in motivation after being diagnosed, so from that the old ODHA who have had high motivation in living their lives gathered in the Surabaya mahameru foundation they support each other new PLHIV so that in the future they can be motivated to return to healthy life and passion in living his life. The results of the study found that the support of long-standing PLHIV plays a very important and successful role in fostering new PLHIV motivation to return to normal life, this is based on interpersonal communication carried out by old PLWHA towards new PLWHA having several important elements that are the center of attention, namely verbal and good non-verbal as well as five positive attitudes to support the effectiveness of interpersonal communication that occurs, namely openness, empathy, support, positive attitude and equality. Keywords: Interpersonal communication, PLWHA, HIV, AIDS, Mahameru Foundation